Re: Enquirey
- To: mathgroup at smc.vnet.net
- Subject: [mg74823] Re: Enquirey
- From: Jean-Marc Gulliet <jeanmarc.gulliet at gmail.com>
- Date: Fri, 6 Apr 2007 04:26:21 -0400 (EDT)
- Organization: The Open University, Milton Keynes, UK
- References: <ev2anc$k85$1@smc.vnet.net>
Rita Ray wrote: > I am trying to solve two equation with two unknowns. I am using > Mathematica 5.2. Below is my program > > > Solve[{a*Exp[2*w]-a^2*Exp[w+(x-y)*z]+a^2*Exp[w-(x-y)*z]-a*Exp[w+(x-y)*z]-a*= > Exp[w-(x-y)*z]+a^2*Exp[2*(x-y)]+a-a^2+a^2*x*Exp[w+(x-y)*z] > +a^2*x*Exp[w-(x-y)*z]-a*x*Exp[w+(x-y)*z]-a*x*Exp[w-(x-y)*z]+2*a*x-2*a^2*x-(= > (a^3*w*Exp[w+(x-y)*z])/z)-((a^3*w*Exp[w-(x-y)*z])/z)+((a^2*w*Exp[w+(x-y)*z]= > )/z)+((a^2*w*Exp[w-(x-y)*z])/z)-((2*a^2*w)/z)+((2*a^3*w)/z)====0,-((a*Exp[-= > w+(x-y)*z]*z*(-((1-a)*w)-2*w*a^2+2*w*a^3+a^2*w*Exp[w-(x-y)*z]-a^3*w*Exp[w-(= > x-y)*z]+a^2*w*Exp[w+(x-y)*z]-a^3*w*Exp[w+(x-y)*z]+a*z-a^2*z+a*z*Exp[2*w]+a^= > 2*z*Exp[2*(x-y)]-a*z*Exp[w-(x-y)*z]+a^2*z*Exp[w-(x-y)*z]-a*z*Exp[w+(x-y)*z]= > -a^2*z*Exp[w+(x-y)*z]+2*a*x*z-2*a^2*x*z-a*x*z*Exp[w-(x-y)*z]+a^2*x*z*Exp[w-= > (x-y)*z]-a*x*z*Exp[w+(x-y)*z]+a^2*x*z*Exp[w+(x-y)*z]))/(a*Exp[-w+(x-y)*z]+(= > 1-a)*Exp[-w-(x-y)*z]))-(a*Exp[-w+(x-y)*z]*((1-a)*z*Exp[-w-(x-y)*z]-a*z*Exp[= > -w+(x-y)*z])*(-((1-a)*w)-2*w*a^2+2*w*a^3+a^2*w*Exp[w-(x-y)*z]-a^3*w*Exp[w-(= > x-y)*z]+a^2*w*Exp[w+(x-y)*z]-a^3*w*Exp[w+(x-y)*z]+a*z-a^2*z+a*z*Exp[2*w]+a^= > 2*z*Exp[2*(x-y)]-a*z*Exp[w-(x-y)*z]+a^2*z*Exp[w-(x-y)*z]-a*z*Exp[w+(x-y)*z]= > -a^2*z*Exp[w+(x-y)*z]+2*a*x*z-2*a^2*x*z-a*x*z*Exp[w-(x-y)*z]+a^2*x*z*Exp[w-= > (x-y)*z]-a*x*z*Exp[w+(x-y)*z]+a^2*x*z*Exp[w+(x-y)*z]))/(a*Exp[-w+(x-y)*z]+(= > 1-a)*Exp[-w-(x-y)*z])^2+(a*Exp[-w+(x-y)*z]*(-2*a^2*z*Exp[2*(x-y)]+a^2*w*z*E= > xp[w-(x-y)*z]-a^3*w*z*Exp[w-(x-y)*z]-a^2*w*z*Exp[w+(x-y)*z]+a^3*w*z*Exp[w+(= > x-y)*z]-a*z^2*Exp[w-(x-y)*z]+a^2*z^2*Exp[w-(x-y)*z]+a*z^2*Exp[w+(x-y)*z]+a^= > 2*z^2*Exp[w+(x-y)*z]-a*x*z^2*Exp[w-(x-y)*z]+a^2*x*z^2*Exp[w-(x-y)*z] > +a*x*z^2*Exp[w+(x-y)*z]-a^2*x*z^2*Exp[w+(x-y)*z]))/(a*Exp[-w+(x-y)*z]+(1-a)= > *Exp[-w-(x-y)*z])====0},{x,y}] > > > Thank you. > > Rita Ray. > > Ph.D. student > Four equal signs in a row (i.e. ====) does not mean anything in Mathematica. To set up an equation, what you want to use is two equal signs in a row (i.e. ==). Since "Solve deals primarily with linear and polynomial equations (Online Help)," and Reduce returns the expression unevaluated with the message, "Reduce::nsmet: This system cannot be solved with the methods available to Reduce, you might want to try a different approach, like a numerical solution with NSolve. eqn1 = (-a)*Exp[2*w] - a^2*Exp[w + (x - y)*z] + a^2*Exp[w - (x - y)*z] - a*Exp[w + (x - y)*z] - a*Exp[w - (x - y)*z] + a^2*Exp[2*(x - y)] + a - a^2 + a^2*x*Exp[w + (x - y)*z] + a^2*x*Exp[w - (x - y)*z] - a*x*Exp[w + (x - y)*z] - a*x*Exp[w - (x - y)*z] + 2*a*x - 2*a^2*x - (a^3*w*Exp[w + (x - y)*z])/z - (a^3*w*Exp[w - (x - y)*z])/z + (a^2*w*Exp[w + (x - y)*z])/z + (a^2*w*Exp[w - (x - y)*z])/z - (2*a^2*w)/z + (2*a^3*w)/z == 0; eqn2 = -((a*Exp[-w + (x - y)*z]*z*(-((1 - a)*w) - 2*w*a^2 + 2*w*a^3 + a^2*w* Exp[w - (x - y)*z] - a^3*w* Exp[w - (x - y)*z] + a^2*w* Exp[w + (x - y)*z] - a^3*w* Exp[w + (x - y)*z] + a*z - a^2*z + a*z*Exp[2*w] + a^2*z*Exp[2*(x - y)] - a*z*Exp[w - (x - y)*z] + a^2*z*Exp[w - (x - y)*z] - a*z*Exp[w + (x - y)*z] - a^2*z*Exp[w + (x - y)*z] + 2*a*x*z - 2*a^2*x*z - a*x*z*Exp[w - (x - y)*z] + a^2*x*z*Exp[w - (x - y)*z] - a*x*z*Exp[w + (x - y)*z] + a^2*x*z* Exp[w + (x - y)*z]))/ (a*Exp[-w + (x - y)*z] + (1 - a)* Exp[-w - (x - y)*z])) - (a*Exp[-w + (x - y)*z]* ((1 - a)*z*Exp[-w - (x - y)*z] - a*z*Exp[-w + (x - y)*z])*(-((1 - a)*w) - 2*w*a^2 + 2*w*a^3 + a^2*w*Exp[w - (x - y)*z] - a^3*w*Exp[w - (x - y)*z] + a^2*w*Exp[w + (x - y)*z] - a^3*w*Exp[w + (x - y)*z] + a*z - a^2*z + a*z*Exp[2*w] + a^2*z*Exp[2*(x - y)] - a*z*Exp[w - (x - y)*z] + a^2*z*Exp[w - (x - y)*z] - a*z*Exp[w + (x - y)*z] - a^2*z*Exp[w + (x - y)*z] + 2*a*x*z - 2*a^2*x*z - a*x*z*Exp[w - (x - y)*z] + a^2*x*z*Exp[w - (x - y)*z] - a*x*z*Exp[w + (x - y)*z] + a^2*x*z*Exp[w + (x - y)*z]))/ (a*Exp[-w + (x - y)*z] + (1 - a)* Exp[-w - (x - y)*z])^2 + (a*Exp[-w + (x - y)*z]*(-2*a^2*z*Exp[2*(x - y)] + a^2*w*z*Exp[w - (x - y)*z] - a^3*w*z*Exp[w - (x - y)*z] - a^2*w*z*Exp[w + (x - y)*z] + a^3*w*z*Exp[w + (x - y)*z] - a*z^2*Exp[w - (x - y)*z] + a^2*z^2*Exp[w - (x - y)*z] + a*z^2*Exp[w + (x - y)*z] + a^2*z^2*Exp[w + (x - y)*z] - a*x*z^2*Exp[w - (x - y)*z] + a^2*x*z^2* Exp[w - (x - y)*z] + a*x*z^2* Exp[w + (x - y)*z] - a^2*x*z^2* Exp[w + (x - y)*z]))/(a*Exp[-w + (x - y)*z] + (1 - a)*Exp[-w - (x - y)*z]) == 0; Reduce[{eqn1, eqn2}, {x, y}] Regards, Jean-Marc